Removal of total coliforms, thermotolerant coliforms, and helminth eggs in Swine production wastewater treated in anaerobic and aerobic reactors - Zacarias Sylvestre, Silvia Helena [UNESP]; Lux Hoppe, Estevam Guilherme [UNESP]; de Oliveira, Roberto Alves [UNESP] (International Journal Of Microbiology, 2014)
The present work evaluated the performance of two treatment systems in reducing indicators of biological contamination in swine production wastewater. System I consisted of two upflow anaerobic sludge blanket (UASB) reactors, with 510 and 209 L in volume, being serially arranged. System II consisted of a UASB reactor, anaerobic filter, trickling filter, and decanter, being also organized in series, with volumes of 300, 190, 250, and 150 L, respectively. Hydraulic retention times (HRT) applied in the first UASB reactors were 40, 30, 20, and 11 h in systems I and II. The average removal efficiencies of total and thermotolerant coliforms in system I were 92.92% to 99.50% and 94.29% to 99.56%, respectively, and increased in system II to 99.45% to 99.91% and 99.52% to 99.93%, respectively. Average removal rates of helminth eggs in system I were 96.44% to 99.11%, reaching 100% as in system II. In reactor sludge, the counts of total and thermotolerant coliforms ranged between 10(5) and 10(9) MPN (100 mL)(-1), while helminth eggs ranged from 0.86 to 9.27 eggs g(-1) TS.